Parachute resistance training: A method to improve the running speed of football players - Ketut Chandra Adinata Kusuma; I Kadek Happy Kardiawan; I Made Satyawan (Journal Sport Area, 2021)
The problem raised is the absence of data on the implementation of resistance parachute-assisted training methods that can increase the short running speed of amateur football players. This study aims to determine the effect of parachute resistance assisted training methods on running speed. This type of research is quantitative with a quasi-experimental research method with the modified pre-test-post-test group design. The subjects of this study are 10 male amateur football players aged 18-20 years. The test instrument in this study is to measure the running speed using the 30 meters sprint test. Data are analyzed using t-test paired sample t-test at a significance level of 5%. The results of data analysis show that the parachute resistance assisted training method has an effect on running speed (sig value = 0.000). Thus, the parachute resistance assisted training method is suitable to be applied to increase the running speed of amateur football players. This research can be further developed by increasing the number of samples and applied to professional football players.